Service-providing occupations, offshoring, and the labor market. - Moncarz, Roger J.; Wolf, Michael G.; Wright, Benjamin (Monthly Labor Review, 2008)
The article identifies 160 occupations considered susceptible to offshoring in the U.S. It discusses trends in historical and projected data for those occupations. It highlights the efforts of the Bureau of Labor Statistics (BLS) to examine all factors affecting employment in industries and occupations, particularly the offshoring of service-providing occupations. The BLS offshoring scoring system which identifies characteristics that make an occupation susceptible to being offshored is also addressed.